Pioneering Role of Nanopore Single-Molecule Sensing in Environmental and Food Surveillance - Wenqiang Tian; Xu Wang; Yan Zhang; Ting Weng; Tlili Chaker; Xiaohan Chen; Qingke Kong; Deqiang Wang (Biosensors)
In recent years, environmental and food safety have garnered substantial focus due to their intimate connection with human health. Numerous biosensors have been developed for identifying deleterious compounds; however, these biosensors reveal certain limitations. Nanopore sensors, featuring nano-scaled pore size, have demonstrated outstanding performance in terms of rapidity, sensitivity, and selectivity as a single-molecule technique for environmental and food surveillance. In this review, we present a comprehensive overview of nanopore applications in these two fields. To elucidate the pioneering roles of nanopores, analytes are categorized into three distinct groups, including metal ions, synthetic contaminants, and biotoxins. Moreover, a variety of strategies are involved, such as the coalescence with ligand probes, the implementation of chemical reactions, the functionalization of nanopores, etc. These scientific studies showcase the versatility and diversity of the nanopore technique, paving the way for further developments of nanopore technology in environmental and food safety.